2001
DOI: 10.1007/s100380170030
|View full text |Cite
|
Sign up to set email alerts
|

The Hemoglobin O mutation in Indonesia: distribution and phenotypic expression

Abstract: We have investigated hemoglobin O Indonesia (HbO Ina ) in related ethnic populations of the Indonesian archipelago: 1725 individuals of the five ethnic populations of South Sulawesi (Bugis, Toraja, Makassar, Mandar, and Kajang) and 959 individuals of the neighboring islands, who were divided into five phylogenetic groups: (a) Batak; (b) Malay from Padang, Pakanbaru, and Palembang in the island of Sumatra; (c) Javanese-related populations (Java, Tengger, and Bali) from the islands of Java and Bali; (d) populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This finding indicates that the distribution of Hb O-Indonesia is partly attributable to geographic and/or ethnic backgrounds. In addition, the phenotypic expression of this variant exhibited normal or asymptomatic mild erythrocytosis features, same as findings in Indonesia and India [20,21,24]. This study's data and the previous study indicated that Hb O-Indonesia does not present any hematological or clinical problem.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding indicates that the distribution of Hb O-Indonesia is partly attributable to geographic and/or ethnic backgrounds. In addition, the phenotypic expression of this variant exhibited normal or asymptomatic mild erythrocytosis features, same as findings in Indonesia and India [20,21,24]. This study's data and the previous study indicated that Hb O-Indonesia does not present any hematological or clinical problem.…”
Section: Discussionsupporting
confidence: 87%
“…Seven hemoglobin variants found in [32,37,[42][43][44][45][46] Northern Thai case [28,47,48] Hb C Data from previous studies this study were previously reported in other regions of Thailand, except for Hb O-Indonesia (Table 4). Hb O-Indonesia (a 116 Glu-Lys ), also known as Hb Burginese-X or Hb Oliviere, has been identified in Indonesian, Indian, Iranian, Italian, and Chinese people [10,17,[19][20][21][22][23][24]. The Thai population has a unique ethnic mosaic, especially southern Thailand, where the majority of the population is composed of Buddhists and Muslims and inhabited by Mongoloids, same as the rest of the Malay peninsula and the Indonesian [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of negatively charged glutamic acid by positively charged lysine at residue 116 is structurally significant and thus can potentially lead to a functional or assembly defect. The previous studies demonstrated that the Hb O mutation is associated with either the instability of a OIna -globin chain or less efficient assembly of the hemoglobin in vivo [6], which is also observed as a consequence of Hb E mutation due to the changes in Glu26Lys amino acid in the b-globin chain. Hb O Indonesia was also found in combination with Sickle Hemoglobin (Hb S) in an Indian family, where the newborn infant was seen to have reduced Hb levels and need to be followed up.…”
Section: Discussionmentioning
confidence: 99%
“…The internal standard for the nuclear DNA was a pGEMT-easy vector with a 123-bp PCR-amplified insert of the α1-globin gene, which had lost the HinfI restriction site at codon 116. This mutation is rare and found only in individuals with Hemoglobin O Indonesia (HbO Ina ), which is restricted to the populations of South Sulawesi (Daud et al 2001), and thus should not be present in the samples examined in the current study. Fixed amounts (2 pg) of the internal standards for mtDNA and nuclear DNA were coamplified with the DNA samples in serially diluted aliquots of the fibroblast lysates (Zhang et al 1996;Filser et al 1997).…”
Section: Quantitation Of the Poly [C] Length Variantmentioning
confidence: 92%
“…The amplification was carried out for 28 cycles of denaturation for 20 s at 95°C (first cycle 5 min at 95°C), annealing for 20 s at 62°C, elongation for 1 min at 72°C (last cycle 5 min at 72°C), followed by 5min at 95°C and 5 min at 25°C for final denaturation and slow annealing. The quantitation of the nuclear DNA was performed by using the primer pair HbO and Alf1 (Daud et al 2001) resulting in a 123-bp fragment. The PCR amplification was carried out for 34 cycles of denaturation at 95°C for 30 s (the first cycle 95°C for 5 min), annealing and elongation at 70°C for 30 s (first cycle 70°C for 1 min; last cycle 70°C for 5 min), followed by final denaturation at 95°C for 5 min, and slow annealing at 25°C for 5min.…”
Section: Quantitation Of the Poly [C] Length Variantmentioning
confidence: 99%